ImplementasiProgramBantuanSosialDiKecamatanBakung Serumpun Kabupaten Lingga Tahun 2025 - Shahibunnahar .; Nazaki .; KhairiRahmi . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT) in Bakung Serumpun District, Lingga Regency in 2025 and identify factors influencing their implementation. Thestudyused a descriptive method with a qualitative approach and George C. Edward III's policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. Data were obtained through interviews and documentation. The results indicate that program implementation has been running quite well, but not optimally. Obstacles encountered include limited human resources, the unavailability of permanent social assistants, suboptimal beneficiary data updates, and inter-agency coordination that still needs to be strengthened. Nevertheless, communication between implementers, apparatus commitment, and program implementation based on technical instructions have supported the implementation of social assistance. Therefore, strengthening coordination, increasing human resource capacity, and regular data updates are needed to ensure more effective, transparent, and targeted aid distribution.